Faktor-Faktor Yang Mempengaruhi Cakupan ASI Eksklusif di Masa Pandemi Covid 19 - Nurul Prihastita Rizyana; Fadillah Ulva (STIKes MERCUBAKTIJAYA, 2022)
The imposition of restrictions on community activities during the Covid-19 pandemic has caused various concerns and anxiety for many people, including mothers who are breastfeeding. In an effort to break the chain of transmission of Covid-19, it is necessary to apply health protocols, one of which is physical distancing. This is feared to cause fear in nursing mothers to breastfeed their babies. The purpose of this study was to determine the factors that affect the coverage of exclusive breastfeeding during the Covid-19 pandemic in the Nanggalo Health Center Work Area, Padang City. The type of research used is quantitative with a cross sectional study design. This research was conducted in the Working Area of ​​the Nanggalo Health Center, Padang City. The number of samples is 67 people. The data used are primary data and secondary data. The measuring instrument used is a questionnaire. Data were analyzed by univariate and bivariate using Chi Square test. The results showed that there was a relationship between the level of knowledge (p=0.001, employment status (0.008), parity (0.015) and husband's support (p=0.049) with exclusive breastfeeding. It is necessary to provide information education to breastfeeding mothers about the importance of exclusive breastfeeding during pregnancy. Covid-19 pandemic.